Experience with shared teaching materials for software engineering across countries - Bothe, Klaus; Schützler, Kay; Budimac, Zoran; Ivanović, M; Putnik, Z; Stoyanov, Stanimir; Stoyanova-Doyceva, Asya; Zdravkova, Katerina; Jakimovski, Boro; Bojić, D; Jurca, Ioan; Kalpić, D; et al. (My University, 2009)
Shared teaching materials are a means to save effort for its development, to transfer methodological and technical knowledge between different university staff, and to exchange experience in practical application. However, does it really pay off considering the diversity of different educational environments and the difficulties of using externally produced materials rather than dedicated individual ones? This paper reports on the extensive experience gained in a multi-country project.
Keywords: International cooperation, shared teaching materials, software engineering